Strategi Pengembangan Program Muhadharah dalam Penguatan Karakter Religius Siswa di MA Darul Ulum Wanayasa - Lestari, Elda Sri; Effendi, Muhamad Ridwan; Setiawan, Usep (Addabani: Interdisciplinary Journal of Islamic Education, 2023)
Various educational problems exist caused by the need to strengthen students' character, one of which is the weakening of religious morality. To instil these religious character values, a character-strengthening strategy is needed, as in Madrasah Aliyah Darul Ulum; character strengthening is carried out through the development of muhadharah programs. Based on this, the research aims to determine the strategy and impact of developing the muhadharah program at MA Darul Ulum Wanayasa to strengthen students' religious character. This research uses a mixed method with ADDIE analysis techniques and religious character theory from Charles Y. Glock dan Rodney W. Stark. Based on the study, the muhadharah development program strategy already has a pattern of analysis, design, development, implementation, and evaluation. Second, the impact of the muhadharah program development strategy can influence strengthening students' religious character aspects of student obedience, increasing student tolerance, and students' harmonious character.